Six Sigma and innovation performance: A conceptual framework based on the absorptive capacity theory perspective - Yusr, Maha Mohammed; Othman, Abdul Rahim; Mohd Mokhtar, Sany Sanuri (Springfield publishers, 2011)
Achieving high rate of performance is the aim of any organization, especially under the pressure of competition. In this regards, innovative abilities of any organization is considered as the leverage of the competitive abilities. The organization’s innovative abilities have drawn the attention of the scholars and practitioners over last decade. Trying to link between innovative abilities and another organizational discipline is one of the most interesting fields to the scholars. Therefore, the current study tries to evaluate the relationship between innovative abilities of organization and Six Sigma as one of the organizational discipline that belongs to the quality umbrella [1]. Six Sigma is considered as a quality approach which has proved its abilities to positively affect the organizational performance. Thus, the current paper aims to review the literature to introduce a conceptual framework that discuses the relationship between the two fields of the organizational discipline represented by Six Sigma and innovation from the perspective of the Absorptive Capacity Theory. Finally, the study presents some suggestions for further studies that can be conducted in the future.